IMPLEMENTASI SISTEM PELAYANAN IZIN USAHA SECARA TERPADU TERHADAP KUALITAS PELAYANAN PUBLIK PADA DPMPTSP KOTA MEDAN - Muhammad Ikhsan; Novlianun Dly; Nelly Agustina Siregar; Maisyarah (Universitas Majalengka, 2024)
This study aims to analyze the implementation of an integrated business licensing service system and its impact on the quality of public services at the Investment Office and One-Stop Integrated Services (DPMPTSP) of Medan City. The research employed a qualitative descriptive method with data collection through observation, interviews, and documentation. The results showed that the implementation of an integrated system has significantly improved service quality through faster processing times, increased transparency, and reduced bureaucratic complexity. The system implementation has successfully integrated various licensing services into a single platform, resulting in more efficient and effective public service delivery. However, some challenges were identified, including the need for continuous system updates and staff training to maintain optimal service quality.